Hot Topics and Directions of Human Resource Analytics Based on a Hybrid Method (Bibliometric Analysis, Fuzzy Delphi Method and SWARA) - Mona Kardani Malekinezhad; Fariborz Rahimnia; GHasem Eslami; Mohammad Mahdi Farahi (International Journal of Information Science and Management)
Due to the emergence of big data during the recent decades, data analytics played an important role in organizations, especially in human resource management (HRM). Despite increasing attention to data analytics in HRM, there is still a gap in this research scope. According to the dispersion of existing relevant studies, this study aimed to reveal the hot topics, as well as the future directions of this field. Therefore, the present study utilized a hybrid method based on bibliometric analysis (co-word analysis), Fuzzy Delphi, and SWARA (Step-Wise Weight Assessment Ratio Analysis) and evaluated 87 articles from the Scopus database. The co-word results extracted a total of 40 keywords, and then the indicators were measured according to experts' opinions and the fuzzy Delphi method (FDM) and were prioritized using the SWARA method. Based on the analysis results, HR analytics and human resource data analytics are the most important cases, and then people analytics, human capital analytics, workforce analytics, data analytics, big data, analytical competencies, predictive HR analytics capability, and HR analyst are ranked third to tenth. The top 6 keywords for future directions are strategy, HR processes, big data, competencies, technology, and evidence.